Los pliegos de condiciones en el contrato de obra (2021)
As a result of the implementation of bidding documents in public procurement, it is intended to establish, from a legal point of view, what is the legal nature of the bidding documents, as well as their strengths, weakness and create proposals for the solutions of the latter. With this purpose, the following research question is proposed: what have been the strengths and weaknesses of the bidding documents in the public bidding selection process from framework of the works contract? For this reason, it is considered that, despite the deficiencies of this administrative act, due to corruption in public procurement, bidding documents are an essential element. For the purpose of the foregoing, the preparation of bidding documents should not be headed by and at the discretion of the contracting entity; on the contrary, there should be an institution in charge of preparing them, together with the inspection and surveillance by a control entity, who ensures transparency, the correct application of the rules and principles governing public procurement, in order to eradicate the political, personal and clientelistic interests that monopolize the contracting and that the interests of the state prevail. The content of the article is the result of a qualitative research methodology, since it was carried out with the purpose of interpreting, identifying and developing the research problem; in addition, it is of a dogmatic nature, taking into account that we studied the legal system of the bidding documents, in order to transmit, use, improve and complement the knowledge.